Little Evidence of Zika Virus Infection in Wild Long-Tailed Macaques, Peninsular Malaysia - Chua, Chong Long; Chan, Yoke Fun; Andu, Eva S.G. Soh; Rovie-Ryan, Jeffrine J.; Sitam, Frankie Thomas; Verasahib, Khebir; Sam, I-Ching (National Library of Medicine, 2019)
We tested a sample of 234 wild long-tailed macaques (Macaca fascicularis) trapped in Peninsular Malaysia in 2009, 2010, and 2016 for Zika virus RNA and antibodies. None were positive for RNA, and only 1.3% were seropositive for neutralizing antibodies. Long-tailed macaques are unlikely to be reservoirs for Zika virus in Malaysia.